Allergen Microarray Indicates Pooideae Sensitization in Brazilian Grass Pollen Allergic Patients. - Priscila Ferreira de Sousa Moreira; Katharina Gangl; Francisco de Assis Machado Vieira; Leandro Hideki Ynoue; Birgit Linhart; Sabine Flicker; Helmut Fiebig; Ines Swoboda; Margarete Focke-Tejkl; Ernesto Akio Taketomi; Rudolf Valenta; Verena Niederberger (PLoS ONE)
Background Grass pollen, in particular from Lolium multiflorum is a major allergen source in temperate climate zones of Southern Brazil. The IgE sensitization profile of Brazilian grass pollen allergic patients to individual allergen molecules has not been analyzed yet. Objective To analyze the IgE sensitization profile of a Brazilian grass pollen allergic population using individual allergen molecules. Methods We analyzed sera from 78 grass pollen allergic patients for the presence of IgE antibodies specific for 103 purified micro-arrayed natural and recombinant allergens by chip technology. IgE-ELISA inhibition experiments with Lolium multiflorum, Phleum pratense extracts and a recombinant fusion protein consisting of Phl p 1, Phl p 2, Phl p 5 and Phl p 6 were performed to investigate cross-reactivities. Results Within the Brazilian grass pollen allergic patients, the most frequently recognized allergens were Phl p 1 (95%), Phl p 5 (82%), Phl p 2 (76%) followed by Phl p 4 (64%), Phl p 6 (45%), Phl p 11 (18%) and Phl p 12 (18%). Most patients were sensitized only to grass pollen allergens but not to allergens from other sources. A high degree of IgE cross-reactivity between Phleum pratense, Lolium multiflorum and the recombinant timothy grass fusion protein was found. Conclusions Component-resolved analysis of sera from Brazilian grass pollen allergic patients reveals an IgE recognition profile compatible with a typical Pooideae sensitization. The high degree of cross-reactivity between Phleum pratense and Lolium multiflorum allergens suggests that diagnosis and immunotherapy can be achieved with timothy grass pollen allergens in the studied population.